Implementation of the Flipped Classroom Model to Improve Cognitive Learning Outcomes in Biology Learning - Dian Arisandy Eka Putra Sembiring; Yusuf, Muhammad; Ali Sadikin; Salsabilla, Opella Futri; Rani, Yunita Cahya; Hidayati, Syaidah; Anistia, Cahaya (Bioeduca : Journal of Biology Education, 2025)
21st-century education emphasizes student-centered learning to develop critical thinking, communication, and collaboration skills. However, biology classrooms still largely rely on conventional methods that place the teacher as the primary source of information. This pattern leads to passive and unmotivated students, resulting in low conceptual mastery. To address this situation, learning innovations are needed that can increase student participation and independence in learning. One relevant alternative is the Flipped Classroom model, in which students first study the material through digital media before face-to-face classroom activities take place. This study aims to improve students' understanding and cognitive learning outcomes through the application of the Flipped Classroom model to the topic of environmental change. This study used a classroom action research (CAR) method implemented in two cycles involving 20 fifth-semester students. Data analysis was conducted using the Kolmogorov–Smirnov normality test to ensure data distribution, Levene's homogeneity test to test for equality of variance, and a paired sample t-test with a significance level of 0.05 to determine differences in learning outcomes between cycles. The results of the study showed a significant increase in learning outcomes, with the average value of cycle I (M = 305.91) increasing to (M = 459.55) in cycle II. A paired t-test showed a significant difference between the two cycles (t(10) = -9.34, p < 0.001). Thus, the application of the Flipped Classroom model was proven effective in increasing student engagement, understanding, and cognitive learning outcomes in biology learning.